Cross-sectional and Stratification Patterns Induced by Tidal and River Discharge Changes in a Tidal Channel: A Modelling Study - Vaz, N.
A 3D baroclinic model (Mohid) was used to perform hindcast simulations in a tidal channel – the Espinheiro Channel (located within Ria de Aveiro, north coast of Portugal) – in order to study the effect of tidal variability and river inflow on the hydrography of the lower portion of the channel, near its inlet. The simulations were performed for distinct periods where markedly tides and river discharge occurred. Tidal currents and salinity data were analyzed at the channel’s mouth during several tidal cycles. A flood-ebb asymmetry was found in stratification with higher values on peak flood than on peak ebb. The cross-section structure of the channel’s inlet was found homogeneous in terms of salinity, but lateral differences in current velocity were found with ebb predominance near the south shore and flood predominance near the north shore, producing a exportation (importation) of salt from the channel to the ocean near the south (north) shore. A marked difference in time between sea level, velocity and salinity was also found. These differences are highly variable, strongly depending on the river inflow. All the results are consistent with observations, making the use of 3D models a suitable tool for the study and management of a complex system like the Espinheiro Channel.